Wheat bran fermented by mixed fungal strains improves the digestibility of crude fiber and may benefit the gut health without impacting the growth performance in weaned pigs. Issue 7 (10th March 2021) - Luo, Yuheng; He, Jun; Li, Hua; Lan, Cong; Cai, Jingyi; Chen, Hong; Tian, Gang; Wang, Huifen; Wang, Quyuan; He, Jun; Chen, Daiwen; Yu, Bing; et al.
Abstract : This study was conducted to compare the effect of raw (WB) or mixed fungi-fermented wheat bran (FWB) on the growth, nutrient digestibility and intestinal health in weaned piglets. Abstract : This study was conducted to compare the effect of raw (WB) or mixed fungi-fermented wheat bran (FWB) on the growth, nutrient digestibility and intestinal health in weaned piglets. After the preparation of FWB, twenty-one cross-bred weaned piglets (7.20 ± 0.5 kg) were separated into three groups for a 40-day trial. The pigs in the control group were fed a basal corn-soybean meal diet. For the other two groups, 8% of expanded corn in the basal diet was replaced by equivalent WB or FWB. Results showed that the content of main nutrients and the composition of dietary fiber in FWB improved compared to that for WB. The digestibility of fiber in pigs fed FWB improved ( P < 0.05) compared to the control and/or WB without affecting their growth performance. Both WB and FWB decreased the conditional pathogen ( Streptococcus ) or/and E. coli virulence factor (STb) in the colon compared to control ( P < 0.05), and the ratio of villus height to crypt depth (VCR) in jejunum increased ( P < 0.05). The number of goblet cells, the expression of MUC-1 and pBD1 in jejunal mucosa, and the proportion of blood CD4 + T lymphocyte subset improved ( P < 0.05) by FWB rather than WB. Furthermore, although only WB elevated ( P < 0.05) the concentration of butyrate in the colon, both WB and FWB increased the number of butyrate-producing bacteria ( P < 0.05) compared to the control. Thus, the main advantage of FWB over WB in weaned pigs is its improvement in fiber digestibility.